2010
DOI: 10.1371/journal.pone.0009813
|View full text |Cite
|
Sign up to set email alerts
|

A New Auditory Multi-Class Brain-Computer Interface Paradigm: Spatial Hearing as an Informative Cue

Abstract: Most P300-based brain-computer interface (BCI) approaches use the visual modality for stimulation. For use with patients suffering from amyotrophic lateral sclerosis (ALS) this might not be the preferable choice because of sight deterioration. Moreover, using a modality different from the visual one minimizes interference with possible visual feedback. Therefore, a multi-class BCI paradigm is proposed that uses spatially distributed, auditory cues. Ten healthy subjects participated in an offline oddball task w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
206
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(224 citation statements)
references
References 42 publications
(57 reference statements)
16
206
1
Order By: Relevance
“…When looking at the occipital channels though (figures 10, 11, 12), we can see an early positive deflection about 220 ms after the target stimuli presentation. This aligns with the results of Schreuder et al [7], where it is concluded that in the short 175 ms condition "class difference has shifted toward the frontal areas when compared to the longer 1000 ms ISI condition". Despite using a low-cost EEG device, the performance of the proposed system is comparable to state-of-the-art performance.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…When looking at the occipital channels though (figures 10, 11, 12), we can see an early positive deflection about 220 ms after the target stimuli presentation. This aligns with the results of Schreuder et al [7], where it is concluded that in the short 175 ms condition "class difference has shifted toward the frontal areas when compared to the longer 1000 ms ISI condition". Despite using a low-cost EEG device, the performance of the proposed system is comparable to state-of-the-art performance.…”
Section: Discussionsupporting
confidence: 91%
“…This resulted to the conclusion that bigger ISIs give better selection accuracy. The opposite results were obtained by Schreuder et al [7], when a separate classifier was trained for each condition.…”
Section: Related Workmentioning
confidence: 63%
See 2 more Smart Citations
“…Steady-state visual evoked potentials have been used for binary selection, [48][49][50][51] both discrete and continuous control of a cursor in 2 dimensions, 52 prosthesis control, 53 FES, 54,55 spelling, 56 and environmental control. 57 For patients with impaired vision, various auditory 39,40,[58][59][60][61] and tactile [62][63][64][65] paradigms have been investigated. A few studies are now focused on the critical need to move BCI systems out of the laboratory and into patients' homes, which raises many complex patient, caregiver, and implementation issues.…”
Section: Device Outputmentioning
confidence: 99%